PENGUATAN INOVASI DALAM MENINGKATKAN KINERJA PERUSAHAAN (Studi pada UKM Mebel di Soloraya) - Sari Puspitasari; Rochmi Widayanti; Ratna Damayanti (Universitas Slamet Riyadi, 2020)
The aim of the study was to determine the influence of market orientation innovation, and the partial and simultaneous marketing strategies on the performance of furniture companies in Soloraya. This research was conducted on UKM furniture at Soloraya. The type of data used is quantitative data. The data source used is primary data. The data collection techniques in this study used questionnaires. Data analysis techniques using multiple linear analyses. The results of this study showed a partial market-oriented significant value of 0.001 < 0.05 then the market orientation was significant to influence the company's performance. A significant value of innovation 0.004 < 0.05 The innovation affects the company's performance, and a marketing strategy variable with a significant rate of 0.000 < 0.05 means that the marketing strategy variable significantly affects the company's performance Furniture at Soloraya. We recommend that UKM furniture in Soloraya more create a new design to improve product competitiveness and product uniqueness in accordance with the wishes of consumers.